A metabolically engineered bacterium controls autoimmunity and inflammation by remodeling the pro-inflammatory microenvironment - Das, Jugal Kishore; Guo, Fengguang; Hunt, Carrie; Steinmeyer, Shelby; Plocica, Julia A; Kobayashi, Koichi S.; Ding, Yufang; Jayaraman, Arul; Ficht, Thomas A; Alaniz, Robert C.; de Figueiredo, Paul; Song, Jianxun (Gut Microbes, 2022)
Immunotherapy has led to impressive advances in the treatment of autoimmune and pro-inflammatory disorders; yet, its clinical outcomes remain limited by a variety of factors including the pro-inflammatory microenvironment (IME). Discovering effective immunomodulatory agents, and the mechanisms by which they control disease, will lead to innovative strategies for enhancing the effectiveness of current immunotherapeutic approaches. We have metabolically engineered an attenuated bacterial strain (i.e., 16M ∆ , Bm∆ ) to produce indole, a tryptophan metabolite that controls the fate and function of regulatory T (T ) cells. We demonstrated that treatment with Bm∆ polarized macrophages (Mφ) which produced anti-inflammatory cytokines (e.g., IL-10) and promoted T function; moreover, when combined with adoptive cell transfer (ACT) of T cells, a single treatment with our engineered bacterial strain dramatically reduced the incidence and score of autoimmune arthritis and decreased joint damage. These findings show how a metabolically engineered bacterium can constitute a powerful vehicle for improving the efficacy of immunotherapy, defeating autoimmunity, and reducing inflammation by remodeling the IME and augmenting T cell function.